Beckman Mark V Atmosphere Analyzer - Dietrich, T. A. (1965)
Beckman originally produced 27 Mark V Atmosphere Analyzers for use on nuclear ballistic missile submarines. The instrument measured oxygen, hydrogen, carbon dioxide, carbon monoxide, freon, and other atmospheric contaminants and completed an analysis ever fifteen minutes. The first photograph appeared in an in-house publication, Feedback, in 1966 and is in the public domain in the United States.
Keywords: Great Britain. Royal Navy; Gases--Analysis; Scientific apparatus and instruments; Submarines (Ships); United States. Navy; Beckman Instruments, Inc.